Black College Women Sexual Health Peer Education at Clark Atlanta University - Clarissa Francis; Josephine Bradley; Christopher Bass; Karla Scipio; Ronald Braithwaite (Georgia Southern University, 2016)
Background: This research was based on the premise that various factors, such as social determinants, cultural competency, use of statistics and location, contribute to the efficacy of the transmission of sexual health education. In the United States, African American women account for 60% of the cases of human immunodeficiency virus (HIV) of women. Considerable research has noted the high rates of HIV among African-American women. The present research, however, focused exclusively on Black college women at Clark Atlanta University (CAU). Methods: A mixed method approach using surveys and participant observation in an exploratory case study was used to evaluate responses of Black college women at CAU to sexual health peer education. Results: Most of the Black college women who attended an event sponsored by Health Services, the Health Peers Educating and Encouraging Responsible Students (H-PEERS), reported that it effectively impacted their overall sexual health. Conclusions: Although, the female students reported having prior knowledge of sexual health information prior to attending CAU, including risk reduction behaviors, they reported participating in sexual risky behaviors. Many of the female students whom reported attending an event sponsored by the H-PEERS effectively had an impact on their sexual health knowledge, attitudes and beliefs towards sex, sexual behaviors, and sexual health status. Further research is needed on how the overall sexual health of black college women at Historically Black Colleges and Universities (HBCU) and predominantly white schools (PWI), and how strategies, such as peer-led health education, differ in transmission and efficacy.